2016
DOI: 10.1177/0003489416636128
|View full text |Cite
|
Sign up to set email alerts
|

Sialolithiasis in an Accessory Submandibular Gland Identified by Magnetic Resonance Sialography

Abstract: This is the first case reported to date in the English literature of a patient with sialolithiasis within an accessory submandibular gland diagnosed by MR-Si.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(22 citation statements)
references
References 12 publications
(22 reference statements)
0
22
0
Order By: Relevance
“…Two case reports have utilized MR sialography to identify accessory submandibular glands [2 , 3 , 8] . However, in both instances, there was unilateral duplication of the submandibular gland with an accessory duct joining the main submandibular duct distal to the papilla.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two case reports have utilized MR sialography to identify accessory submandibular glands [2 , 3 , 8] . However, in both instances, there was unilateral duplication of the submandibular gland with an accessory duct joining the main submandibular duct distal to the papilla.…”
Section: Discussionmentioning
confidence: 99%
“…Reports have also described a pleomorphic adenoma as the initial cause of submandibular swelling leading to identification of submandibular accessory glands [5 , 6] . The majority of cases of duplicate submandibular glands we identified through literature review were evaluated with conventional sialography, with only 2 reported cases evaluated concurrently with MR sialography [3 , 7 , 8] .…”
Section: Introductionmentioning
confidence: 99%
“…In both entities, low prevalence results in few searches, which contributes to their relative obscurity. Of the published works, some refer to findings during anatomical dissection ( 14 , 15 ), others to the presence of pathology in those areas: obstructive alterations such as sialolithiasis ( 11 , 16 , 17 ) or even tumors, for example the presence of a mixed tumor ( 2 , 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…MR Sialography is currently accepted as the best method for studying the salivary glands ( 11 , 22 ) and can be used to detect accessory glands and ducts, but is not a standard first imaging procedure owing to its cost. However, as a non-invasive imaging test, without the need for ionizing radiation, and with a high capacity for tissue discrimination, which allows it to identify in detail not only the glandular tissue but also the ductal system of the submaxillary gland ( 11 ), it seems an optimal procedure to rule out this anatomical variant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation